A case report: Paediatric surfer's myelopathy. (January 2018) - Scatchard, Rebecca; Alves Rosa, Joao; Bowen, Philippa; Mortimer, Alex; Sharples, Peta M.; Lux, Andrew L.
Abstract: Surfer's myelopathy was first described by Thompson et al., in 2004. 1 It is a rare cause of sudden spinal cord injury that occurs in the absence of direct trauma to the spinal area in novice healthy surfers. We present the case of the youngest patient we are aware of to be diagnosed with surfer's myelopathy following actual surfing. A clear aetiology for surfer's myelopathy has not previous been described. However, the hypothesis that there is ischaemia to the lower spinal cord is supported by our case, where we present the first clear angiographic evidence of the occlusion of the great anterior radicular artery of Adamkiewicz in a patient diagnosed with surfer's myelopathy. Highlights: One of the youngest reported cases of surfer's myelopathy. Clear radiological evidence of occluded artery of Adamkiewicz. This supports the hypothesis that surfer's myelopathy is, in some cases, caused by occlusion of a major spinal artery.